2006
DOI: 10.2337/db06-0373
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Matrix Metalloproteinase 3 (MMP3) in Preadipocytes/Stromal Vascular Cells From Nonobese Nondiabetic Versus Obese Nondiabetic Pima Indians

Abstract: Prior microarray studies comparing global gene expression patterns in preadipocytes/stromal vascular cells isolated from nonobese nondiabetic versus obese nondiabetic Pima Indians showed that matrix metalloproteinase 9 (MMP9) is upregulated in obese subjects. The current study targeted analysis of nine additional MMP genes that cluster to a region on chromosome 11q22 that is linked to BMI and percent body fat. Differential-display PCR showed that MMP3 is downregulated in preadipocytes/stromal vascular cells fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 23 publications
4
25
2
Order By: Relevance
“…A recent study reported that the MMP-3 expression levels are negatively correlated with percent body fat, and the MMP-3 gene variants are associated with both BMI and type 2 diabetes in Pima Indians. 28 The mice with transplanted cultured 3T3-L1 cells showed that the transplanted adipocytes in the visceral space, and Macrophage MMP-3 for the function of adipocytes H Unoki et al not subcutaneous space, increased TNF-a gene expression. 5 A microarray analysis revealed that the MMP-3 gene expression is drastically induced in addition to TNF-a.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that the MMP-3 expression levels are negatively correlated with percent body fat, and the MMP-3 gene variants are associated with both BMI and type 2 diabetes in Pima Indians. 28 The mice with transplanted cultured 3T3-L1 cells showed that the transplanted adipocytes in the visceral space, and Macrophage MMP-3 for the function of adipocytes H Unoki et al not subcutaneous space, increased TNF-a gene expression. 5 A microarray analysis revealed that the MMP-3 gene expression is drastically induced in addition to TNF-a.…”
Section: Discussionmentioning
confidence: 99%
“…The largest two-dimensional MLS for the stringent phenotype was detected in region 11q22, which previously has been implicated as conferring susceptibility to T2DM (Traurig et al 2006) and T1DM (Dong et al 2007), and in region 21q21, which has been suggested as a potential locus for T1DM (Bergholdt et al 2005). Similarly, the largest two-dimensional MLS for the broad phenotype was detected on chromosomes 12q24 and 20q13.…”
Section: Susceptibility Loci For Diabetes-related Traitsmentioning
confidence: 87%
“…Chromosome 4p15 has been suggested as a susceptibility region for T2DM (Wiltshire et al 2004), and 7q31 has been suggested to carry a susceptibility locus for metabolic syndrome (Loos et al 2003) and for fasting insulin levels (Lakka et al 2003). The largest two-dimensional MLS for the stringent phenotype was detected in region 11q22, which previously has been implicated as conferring susceptibility to T2DM (Traurig et al 2006) and T1DM (Dong et al 2007), and in region 21q21, which has been suggested as a potential locus for T1DM (Bergholdt et al 2005). Similarly, the largest two-dimensional MLS for the broad phenotype was detected on chromosomes 12q24 and 20q13.…”
mentioning
confidence: 84%
“…A candidate gene study on the role of MMP3 gene variants in obesity was published in a population of adult Pima Indians, 18 while no study has yet been performed in adult Caucasians or in children. The authors reported that variants rs650108 and rs522616 of MMP3 gene were associated with both BMI and type 2 diabetes under a dominant model.…”
Section: Mmp3 and Adiposity Indices In European Children D Cugino Et Almentioning
confidence: 99%
“…16,17 Experimental studies demonstrated that mouse MMP3 is involved in adipose tissue formation and that changes in its expression could be related to obesity-mediated adipose tissue remodeling. 12 Moreover, a study conducted in Pima Indians 18 showed that MMP3 gene was expressed in preadipocytes/stromal vascular cells and its expression was associated with variations in body fat. Therefore, we investigated the association of MMP3 gene polymorphisms with BMI and other indices of adiposity, not yet investigated in Caucasian adults or in children, in the largest prospective European cohort of children established to date, participating in the Identification and Prevention of Dietary-and Lifestyle-Induced Health Effects in Children and Infants (IDEFICS) project.…”
Section: Introductionmentioning
confidence: 99%